PENGARUH PRESTASI BELAJAR TERHADAP MINAT BERWIRAUSAHA DI BIDANG TATA BOGA - Putri, Hana Rahma (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study was to determine (1) the learning achievement of Indonesian cake and cake subjects in the culinary field; (2) students' entrepreneurial interest in Indonesian cake and cake subjects in the culinary field; and (3) the effect of learning outcomes in cake and cake subjects. Indonesia is in the field of catering and has an interest in entrepreneurship. This research belongs to the type of ex-post facto research. Methods of data collection used questionnaires and documentation. The data analysis technique used descriptive analysis techniques and hypothesis testing using the Product Moment correlation test which was preceded by the analysis prerequisite tests, namely normality and linearity tests. The results showed that (1) the learning achievement of Indonesian cake and pastry subjects in the culinary field was in the high category with an average score of 81.37; (2) Students' entrepreneurial interest in Indonesian cake and pastry subjects in the culinary field is in the sufficient category with an average score of 55.15; (3) There is an effect of learning outcomes for Indonesian cake and pastry subjects in the field of culinary arts with entrepreneurial interest with the value of r arithmetic